Forecasting Public Sector Accountability: Analyzing and Predicting Audit Trends in Rwanda's Financial Management (2020-2030) - Celestin, Mbonigaba; Sujatha, S.; Kumar, A. Dinesh; Vasuki, M. (Rabi Sangyan, 2024)
This study provides a comprehensive analysis of the evolution of public financial management in Rwanda, focusing on the period from 2020 to 2030. Utilizing data from the Office of the Auditor General (OAG) and qualitative assessments, the research examines key trends in financial accountability, including audit opinions, compliance with laws, value for money, and the implementation of audit recommendations. The findings indicate significant progress in Rwanda's public financial management, evidenced by an increase in unqualified audit opinions and a reduction in financial mismanagement. These improvements are attributed to enhanced internal controls, strengthened financial regulations, and a heightened focus on value-for-money audits. Employing predictive modeling, the study forecasts continued positive trends, anticipating near-complete adherence to financial regulations and further reductions in mismanaged public funds by 2030. The study concludes with strategic recommendations aimed at sustaining these improvements, including further strengthening internal controls, enhancing compliance monitoring, and leveraging advanced technology for financial oversight. These recommendations are intended to support Rwanda’s ongoing efforts to achieve its 2030 development goals by ensuring efficient and transparent management of public resources.